2006
DOI: 10.1016/j.ijsu.2006.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates in dysvascular lower limb amputees

Abstract: Our study indicates that the median survival remains at 4years, which is similar to the previously published evidence in the Finish study of 1998 and the earlier study from Scotland in 1992. Unlike the previous data, our study indicates that patients with BK amputations have a higher hazard ratio than the AK amputees, and an association with diabetes has poorer prognosis regarding survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 3 publications
1
37
2
3
Order By: Relevance
“…Torburn et al [23] found that individuals with traumatic TTA were of better physical fitness because their amputations were not due to medical conditions or behaviors that typically affect metabolic rate (e.g., diabetes, peripheral vascular disease, smoking [24]). In the military, a majority of amputations are traumatic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Torburn et al [23] found that individuals with traumatic TTA were of better physical fitness because their amputations were not due to medical conditions or behaviors that typically affect metabolic rate (e.g., diabetes, peripheral vascular disease, smoking [24]). In the military, a majority of amputations are traumatic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of DTI strongly depends on the geometrical and biomechanical characteristics of the bone-muscle interface (Gefen, 2007a, b), which differ widely across individual TTA patients due to different surgical techniques, level of amputation, muscle atrophy and scarring (Portnoy et al, 2007). Since approximately 80% of lower limb amputees suffer peripheral vascular disease, diabetes or both (Kulkarni et al, 2006), the neuropathy associated with these diseases prevents patients from detecting pain and injury to their residual limb. Presently, there is paucity of information on mechanical conditions in the residual limb during load-bearing.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patient records in these historical cohort studies was large (n = 174 to n = 21,520) [1][2]4,6,[8][9][10][11]30].…”
Section: Discussionmentioning
confidence: 99%
“…From historical cohort studies the patient survival rate after a lower-limb amputation because of vascular problems is clearly moderate to low over time [1][2][3][4][5][6][7][8][9][10][11][12]. However, prospective studies on lower-limb amputees seldom report their survival rates, inclusion and exclusion criteria, and/or referral and dropout rates (death included) [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%